Life Style-Related Diseases of the Digestive System: Colorectal Cancer as a Life Style-Related Disease: from Carcinogenesis to Medical Treatment - Hirokazu Takahashi; Kyoko Yoneda; Ayako Tomimoto; Hiroki Endo; Toshio Fujisawa; Hiroshi Iida; Hironori Mawatari; Yuichi Nozaki; Tamon Ikeda; Tomoyuki Akiyama; Masato Yoneda; Masahiko Inamori; et al. (Elsevier, 2007)
Life style-related diseases are associated with an increased risk of colorectal cancer (CRC). Recently, an association has been demonstrated between obesity and CRC. CRC has been associated with markers of insulin or glucose control, and insulin resistance might be the unifying mechanism by which several risk factors affect colorectal carcinogenesis. We evaluated the association between the number of aberrant crypt foci (ACF) and obesity, insulin resistance, hyperlipidemia, and other factors of life style-related disease. As a result, age, body mass index (BMI), waist circumference, and visceral fat obesity were significantly associated with the number of ACF. These results suggest that visceral fat obesity is an important target for CRC prevention. Peroxisome proliferator-activated receptor gamma (PPARγ) is a member of the nuclear receptor superfamily and is highly expressed in CRC. PPARγ ligand administration for 1 to 8 months significantly reduced the number of ACF in human subjects. PPARγ ligand is a promising candidate as a chemopreventive agent. Further investigation is needed to elucidate these mechanisms. Keywords:: life style-related disease, colorectal cancer, chemoprevention, aberrant crypt foci (ACF), peroxisome proliferator-activated receptor gamma (PPARγ)